Zakat di Malaysia dalam Perspektif Ekonomi - Nurhasanah, Nurhasanah (Faculty of Shariah and Law, 2012)
Zakah is the implications of the high level of practice Muslims toward the teachings of Islam in Malaysia. It has been carried out since the pre-colonial, colonial times, post-independence, 1957, 80s, and 90s to the present. Regulatory changes are not necessarily Â set zakat source in accordance with the economic development and professional management. In zakah management, government noted that the potential fellowship zakah increased in accordance with the economic progress of the Muslim community. To foster public confidence in the management of zakat, government through the Majelis Islam Wilayah Persekutuan (MAIWIP) established the Center Levy Zakat (PPZ) in 1991 in order to create a profesional zakah management by implementing corporate systems.DOI: 10.15408/aiq.v4i1.2084